Origin of the Newly Discovered Zhunuo Porphyry Cu‐Mo‐Au Deposit in the Western Part of the Gangdese Porphyry Copper Belt in the Southern Tibetan Plateau, SW China. (February 2017) - HUANG, Yong; LI, Guangming; DING, Jun; DAI, Jie; YAN, Guoqiang; DONG, Suiliang; HUANG, Hanxiao
Abstract : Abstract: The newly discovered Zhunuo porphyry Cu‐Mo‐Au deposit is located in the western part of the Gangdese porphyry copper belt in southern Tibet, SW China. The granitoid plutons in the Zhunuo region are composed of quartz diorite porphyry, diorite porphyry, granodiorite porphyry, biotite monzogranite and quartz porphyry. The quartz diorite porphyry yielded zircon U‐Pb ages of 51.9±0.7 Ma (Eocene) using LA‐ICP‐MS, whereas the diorite porphyry, granodiorite porphyry, biotite monzogranite and quartz porphyry yielded ages ranging from 16.2±0.2 to 14.0±0.2 Ma (Miocene). Cu‐Mo‐Au mineralization is mainly hosted in the Miocene granodiorite porphyry. Samples from all granitoid plutons have geochemical compositions consistent with high‐K calc‐alkaline series magmatism. The samples display highly fractionated light rare‐earth element (REE) distributions and heavy REE distributions with weakly negative Eu anomalies on chondrite‐normalized REE patterns. The trace element distributions exhibit positive anomalies for large‐ion lithophile elements (Rb, K, U, Th and Pb) and negative anomalies for high‐field‐strength elements (Nb and Ti) relative to primitive mantle‐normalized values. The Eocene quartz diorite porphyry yielded ∊Nd ( t ) values ranging from –3.6 to –5.2, ( 87 Sr/ 86 Sr)i values in the range 0.7046–0.7063 and initial radiogenic Pb isotopic compositions with ranges of 18.599–18.657 206 Pb/ 204 Pb, 15.642–15.673 207 Pb/ 204 Pb and 38.956–39.199 208 Pb/ 204 Pb. In contrast, the Miocene granitoid plutons yielded ∊Nd ( t ) values ranging from –6.1 to –7.3 and ( 87 Sr/ 86 Sr)i values in the range 0.7071–0.7078 with similar Pb isotopic compositions to the Eocene quart diorite. The Sr‐Nd‐Pb isotopic compositions of the rocks are consistent with formation from magma containing a component of remelted ancient crust. Zircon grains from the Eocene quartz diorite have ∊Hf ( t ) values ranging from −5.2 to +0.9 and two‐stage Hf model ages ranging from 1.07 to 1.46 Ga, while zircon grains from the Miocene granitoid plutons have ∊Hf ( t ) values from −9.9 to +4.2 and two‐stage Hf model ages ranging from 1.05−1.73 Ga, indicating that the ancient crustal component likely derives from Paleo‐ to Mesoproterozoic basement. This source is distinct from that of most porphyry Cu‐Mo‐Au deposits in the eastern part of the Gangdese porphyry copper belt, which likely originated from juvenile crust. We therefore consider melting of ancient crustal basement to have contributed significantly to the formation Miocene porphyry Cu‐Mo‐Au deposits in the western part of the Gangdese porphyry copper belt.